A Cross-Sectional Study on the Relationship Between Timing of Food Intake and Non-Alcoholic Fatty Liver Disease - Hari, Radhika; Marikutty; Giri, P V (International Research Journal of Ayurveda & Yoga, 2022)
Background & Objective: Nowadays, Non-alcoholic fatty liver disease (NAFLD) is becoming the most common liver disease worldwide. In a recent study from the United States (US), the increase in liver mortality was associated with an increased prevalence of non-alcoholic fatty liver disease. It is considered as a Santarpanajanya Vadhi as per Ayurvedic literature. Dietary factors are one of the primary causes for the manifestation of NAFLD. Food timing also matters in the course of disease development. Ayurvedic literature strictly laid down on certain principles and one among them is the Aaharavidhi Vidhanam. It clearly explains the need for taking the food in right time and in the right amount. This study aims to establish the relationship between the timing of food and NAFLD. Methodology: A cross-sectional study was conducted among the 30 participants visiting the Kayachikitsa OPD of Vaidyaratnam Ayurveda College, Ollur diagnosed with NAFLD and enquired about their timing of food. Results & Discussion: Among the 30 participants, 76.7% had irregular food habits in which 68.8% belong to female and 85.7% to male. The odds of irregular food habits in females are more than those in males who are diagnosed with NAFLD, but the p value 0.399 indicates there is no significant gender wise priority while analysing the relation between time of food and NAFLD. Conclusion: This study establishes a positive relationship of time of food intake and NAFLD ie, those who are taking food at an irregular time is tend to develop NAFLD